2016
DOI: 10.1038/ncomms11095
|View full text |Cite
|
Sign up to set email alerts
|

Identification of plant vacuolar transporters mediating phosphate storage

Abstract: Plant vacuoles serve as the primary intracellular compartments for inorganic phosphate (Pi) storage. Passage of Pi across vacuolar membranes plays a critical role in buffering the cytoplasmic Pi level against fluctuations of external Pi and metabolic activities. Here we demonstrate that the SPX-MFS proteins, designated as PHOSPHATE TRANSPORTER 5 family (PHT5), also named Vacuolar Phosphate Transporter (VPT), function as vacuolar Pi transporters. Based on 31P-magnetic resonance spectroscopy analysis, Arabidopsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
196
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(208 citation statements)
references
References 64 publications
11
196
1
Order By: Relevance
“…In A. thaliana there are three members (SPX-MSF1-3). The only characterized member is SPX-MFS1, also known as PHT5, which belongs to the class of vacuolar phosphate transporters [26]. The SPX-MFS1 loss of function mutant has low vacuolar-to-cytoplasm phosphate ratio compared to wild-type plants.…”
Section: The Association Between Spx Domains and Phosphate Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…In A. thaliana there are three members (SPX-MSF1-3). The only characterized member is SPX-MFS1, also known as PHT5, which belongs to the class of vacuolar phosphate transporters [26]. The SPX-MFS1 loss of function mutant has low vacuolar-to-cytoplasm phosphate ratio compared to wild-type plants.…”
Section: The Association Between Spx Domains and Phosphate Metabolismmentioning
confidence: 99%
“…The SPX-MFS1 loss of function mutant has low vacuolar-to-cytoplasm phosphate ratio compared to wild-type plants. Conversely, SPX-MFS1 overexpression leads to misregulation of phosphate starvation-responsive genes and growth retardation as a consequence of phosphate sequestration into vacuoles [26]. The exact function of the SPX domain in this protein is not fully known.…”
Section: The Association Between Spx Domains and Phosphate Metabolismmentioning
confidence: 99%
“…3 Complementary to our results, 31 P-magnetic resonance spectroscopy analysis revealed that loss-of-function of vpt1 mutants accumulated less Pi and exhibited a lower vacuolar-to-cytoplasmic Pi ratio than the wild types. 4 Taken together, these results indicate that the members of SPX-MFS family are the candidate transporters conducting Pi across the tonoplast.…”
mentioning
confidence: 82%
“…During most phases of plant development, Pi concentration is much higher in the vacuole than in the cytosol, indicating that the vacuole has transport proteins responsible for the transport of Pi across tonoplast. 2 Recently, we, 3 Liu et al, 4 and Wang et al 5 independently revealed that SPX-MFS family potentially might function as a new group of vacuolar Pi transporters in plants. SPX-MFS proteins contain an evolutionally conserved SPX domain [named after yeast Syg1 and Pho81 and human xenotropic and polytropic retrovirus receptor 1 (XPR1)] with an MFS (Major Facilitator Superfamily) domain.…”
mentioning
confidence: 97%
See 1 more Smart Citation